(untitled) (Washington, D.C, 1949)
Contents: introduction; A. D. 600 the Middle East in disintegration; The rise and decline of the musium civilization, the ottoman and persian empires, and the growth of European enterprise....
Keywords: Trung Đông,Middle East; Lịch sử,History